Differences between remote and analog design thinking through the lens of distributed cognition - Wolferts, Daniel; Stein, Elisabeth; Bernards, Ann-Kathrin; Reiners, René (Frontiers in Artificial Intelligence, 2022)
Due to the huge surge in remote work all over the world caused by the COVID-19 pandemic, today’s work is largely defined by tools for information exchange as well as new complex problems that must be solved. Design Thinking offers a well-known and established methodological approach for iterative, collaborative and interdisciplinary problem solving. Still, recent circumstances shed a new light on how to facilitate Design Thinking activities in a remote rather than an analogue way. Due to Design Thinking's high production of artifacts and its focus on communication and interaction between team members, the theory of Distributed Cognition, specifically the Distributed Cognition for Teamwork (DiCoT) framework, provides an interesting perspective on the recent going-remote of Design Thinking activities. For this, we first highlight differences of analogue versus remote Design Thinking by analyzing corresponding literature from the recent years. Next, we apply the DiCoT framework to those findings, pointing out implications for practical facilitation of Design Thinking activities in an analogue and remote setting. Finally, we discuss opportunities through artificial intelligence-based technologies and methods.